PENGARUH MOTIVASI DALAM PEMBELAJARAN SD NEGERI 173582 SIGUMPAR KABUPATEN TOBA - Purba, Joen Parningotan; Silalahi, Naomi A; Berutu, Esra D. A (Universitas Quality, 2024)
Motivation is a change in energy within a person which is characterized by the drive that comes from within a person toachieve a goal. Encouragement and business reactions caused by the need to achieve in life. This makes individuals havethe effort, desire and drive to achieve high learning outcomes. Learning outcomes are a reflection of a person's abilityto master the subjects being taught. High learning outcomes are a symbol of a student's success in their studies.Students who have high learning outcomes indicate that they have a high level of mastery of the subjects programmed,and vice versa.For a student to have motivation to learn cannot be separated from one of the basic types of needs, namely the need forachievement. Humans who have a high need for achievement, have a high desire to succeed, dare to take risks, are ableto take over responsibility for tasks, like uniqueness, are agile, tend to be restless, like to work hard, are not afraid toface failure when it happens and have a tendency to assert themselves.There is a general tendency that success and failure have an effect on motivation, namely: (1) motivation increasesfollowing failure among individuals who produce achievement motivation, (2) motivation hinders following failureamong individuals who are low in achievement motivation, (3) motivation decreases following success amongindividuals who are low in generating achievement motivation. So learning motivation as one of the psychologicalfactors also contributes to efforts to achieve learning outcomes. In other words, achieving learning outcomes is actuallythe key to a student's motivation to learn.